Geographical analyses and artificial intelligence for the study of late medieval settlements in Southern Tuscany (Italy) - Luca Deravignone (Belgeo, 2014)
This paper presents how Artificial Neural Networks (ANN), integrated in a GIS platform, has been used to analyse ancient settlement patterns, in particular fortified villages and medieval settlements in central Italy. The idea at the base of this method is that each settlement system can be seen as an outcome of a social and territorial background. Through the use of different data such as satellite images, historical cartography and archaeological evidences, it is possible to individuate, with the help of ANN methodologies, some of the links between human settlements and the territory. This methodology allows a double approach: firstly the analysis of ancient settlement pattern distribution itself, and secondly the identification of undiscovered archaeological sites. Particular focus will be put on evaluation and quantification of the relationship between late medieval castles (Xth-XIIIth Century A.D.) and environmental variables, and between actual and ancient land use, with the integration of satellite imagery, in particular Landsat, and the use of historical cartography.